THE EFFECT OF THE COVID-19 PANDEMIC ON THE TRAVEL BEHAVIOR OF COMMUTER WORKERS IN DKI JAKARTA PROVINCE - Tuankotta, Jamaluddin
On March 11, 2020, the World Health Organization (WHO) officially declared COVID-19 a pandemic. As a result, each country has adopted a travel restriction policy to prevent the spread of the virus, including the Indonesian government. However, due to travel restriction policies, commuter workers have experienced a change in their work and travel. For the Province of DKI Jakarta, which is the center of the Indonesian economy, of course, this has a big impact. This study has the objective to examine how the effect of the COVID-19 pandemic on the travel behavior of commuter workers in DKI Jakarta Province. This study is important because changes in the travel behavior of commuter workers in DKI Jakarta Province can impact traffic. There is a hypothesis about changes in travel behavior during the pandemic and changes in travel behavior in the future after the COVID-19 pandemic ends. There has been a decrease in traffic density during the pandemic on the roads for commuter workers from their residences in the Jabodetabek area to workplaces in DKI Jakarta Province. In addition, the descriptive statistical analysis results found that there has been a decrease in travel time and transportation costs. In the analysis results using cross-tabulation, public transportation users had shifted to private vehicles during the pandemic with a significant value. A large contribution was made by commuter workers with male characteristics, working in the government sector, high income, married, and had children. Meanwhile, the significant value and contribution given by commuter workers who increase the spatial distribution in the form of an increase in the frequency of work from home activities are those who have the employment status of government employees and non-essential types of work. Then, commuter workers with high-income characteristics have significant value and great contribution, increasing temporal distribution by changing commuting time choices.v In the analysis results using PLS-SEM, there are concerns about using public transportation after the pandemic period ends, with a significant value and a large contribution given by the group of commuter workers with low income. The same group also scored significantly and contributed greatly to reducing the duration of face-to-face and teamwork activities. Meanwhile, a significant value to the indicator of the desire to get flexible working hours and travel not during peak hours given by commuter workers with essential work types have contributed considerably. The high number of commuter workers working from home during the pandemic does not follow a desire to continue these activities after the pandemic period ends. This finding raises questions in future research on why working from home is not an option for commuters. Even so, in this study, respondents were interested in reducing the duration of face-to-face and teamwork activities. It is a sign of increasing the spatial distribution with a choice of location other than the house. If the local government wants to keep travel time low, it is necessary to encourage telecommuting policies. For example, improvements in digital facilities can reduce the duration of face-to-face and teamwork activities to continue. In addition, it is also necessary to support locations other than home, which can be alternative places to work such as restaurants, cafes, or co-working spaces. Another policy that can keep travel times low in traffic is to promote flexible working hours so commuters can travel less during peak hours. However, this study found a low number for the temporal distribution factor, even though this policy can solve public transportation users when traveling during a pandemic. In a shift from public transportation users to private vehicles, local governments need to promote public transportation in the recovery phase after the pandemic ends. The free fare policy combined with increased personal vehicle parking rates can be an option for commuters with low and high incomes to switch to public transportation.